2018
DOI: 10.1242/jeb.153130
|View full text |Cite|
|
Sign up to set email alerts
|

Passive water collection with the integument: mechanisms and their biomimetic potential

Abstract: Several mechanisms of water acquisition have evolved in animals living in arid habitats to cope with limited water supply. They enable access to water sources such as rain, dew, thermally facilitated condensation on the skin, fog, or moisture from a damp substrate. This Review describes how a significant number of animals - in excess of 39 species from 24 genera - have acquired the ability to passively collect water with their integument. This ability results from chemical and structural properties of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…A variety of functional materials, such as amphiphilic surfaces and artificial cactus spines, have been developed for saturated (fog) water harvesting, and some novel aerodynamic designs have been inspired by other surface morphologies. For example, Harris et al reported a biomimetic structured surface for atmospheric saturated water harvesting inspired by the Stenocara beetle, which has an irregular textured shell with hydrophilic sites on its hydrophobic shell background. To mimic this unique structure, hydrophobic polystyrene (PS) and hydrophilic poly­(4-vinylpyridine) (P4VP) were subsequently coated on a substrate to afford a dual-layered coating (Figure ). Due to poor compatibility, the P4VP segments tend to minimize its contact areas with PS under high-temperature annealing, resulting in the connection among isolated P4VP spheres on top of the PS layer.…”
Section: Saturated Water Harvestingmentioning
confidence: 99%
“…A variety of functional materials, such as amphiphilic surfaces and artificial cactus spines, have been developed for saturated (fog) water harvesting, and some novel aerodynamic designs have been inspired by other surface morphologies. For example, Harris et al reported a biomimetic structured surface for atmospheric saturated water harvesting inspired by the Stenocara beetle, which has an irregular textured shell with hydrophilic sites on its hydrophobic shell background. To mimic this unique structure, hydrophobic polystyrene (PS) and hydrophilic poly­(4-vinylpyridine) (P4VP) were subsequently coated on a substrate to afford a dual-layered coating (Figure ). Due to poor compatibility, the P4VP segments tend to minimize its contact areas with PS under high-temperature annealing, resulting in the connection among isolated P4VP spheres on top of the PS layer.…”
Section: Saturated Water Harvestingmentioning
confidence: 99%
“…Examples include toads and frogs. Amphibians have developed morphological and behavioural adaptations capable of acting together to maintain the hydric balance [10,56,57]. Amphibians typically absorb water through the skin.…”
Section: (E) Amphibiansmentioning
confidence: 99%
“…The extreme xerophily of tenebrionids has fascinated researchers from a wide variety of fields. As a result species such as the Namibian fog basking beetle ( Onymacris unguicularis Haag) have been incorporated into biology-inspired engineering projects seeking solutions for efficient cooling and hydration systems 11 , 12 . Nevertheless, available studies on this matter are often taxonomically restricted leaving the dazzling potential of darkling beetles largely untouched—especially in the context of larval behaviour and ecology.…”
Section: Introductionmentioning
confidence: 99%